Family dynamics and religious affiliations as a system to reduce substance abuse among adolescents - Onah, Caleb; Mataluwo, Bibian (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
While various theories provide valuable insights into adolescent behavior, they do not fully account for the complex interplay between family dynamics and religious affiliations as a dual system influencing it. This study investigated the influence of religious affiliations and family dynamics in reducing substance abuse among adolescents aged 15-25 years. Using an ex post facto research design, a sample of 400 adolescents was drawn through purposive sampling. Standardized scales were employed to measure religious engagement, family dynamics, and substance abuse behaviors. Data were analyzed using linear regression for the first two hypotheses and multiple regression for the third hypothesis. The results showed that family dynamics significantly predict substance abuse reduction among adolescents (R = 0.464, R² = 0.216, F(1, 398) = 109.151, p < 0.001). Additionally, religious affiliations were found to significantly contribute to substance abuse reduction (R = 0.544, R² = 0.296, F(1, 398) = 167.482, p < 0.001). When combined, family dynamics and religious affiliations also significantly predict substance abuse reduction (R = 0.593, R² = 0.352, F(2, 397) = 107.246, p < 0.001). These findings suggest that religious organizations should actively engage adolescents in activities that promote healthy lifestyles and encourage health-seeking behaviors when addiction is identified. Also, communities should encourage adolescents to participate in youth religious groups, which offer peer support and mentorship grounded in faith-based principles.